AKAP6 controls NFATc4 activity for BDNF-mediated neuroprotection - Joanna Mackiewicz; Julia Tomczak; Malwina Lisek; Feng Guo; Tomasz Boczek (Molecular Brain)
Abstract Brain-derived neurotrophic factor (BDNF) is known for its potent prosurvival effect. Despite successfully replicating this effect in various clinical and pre-clinical models, the complete characterization of the molecular mechanisms underlying its neuroprotective action remains incomplete. Emerging research suggests a vital role for A-kinase anchoring proteins (AKAPs) as central nodal points orchestrating BDNF-dependent signaling. Among the over 50 identified AKAPs, AKAP6 has recently gained special attention due to its involvement in the neurotrophin-mediated survival of injured retinal ganglion cells (RGCs). However, the mechanisms by which AKAP6 responds to pro-survival BDNF signaling remain unknown. In this study, we shown that AKAP6 plays a crucial role in regulating BDNF-mediated NFAT transcriptional activity in neuronal survival by anchoring protein phosphatase calcineurin (CaN) and nuclear factor of activated T cells (NFATc4). Furthermore, we demonstrate that disrupting the anchoring of CaN diminishes the pro-survival effect of BDNF. Lastly, through experiments with NFATc4−/− mice, we provide evidence that NFATc4 acts downstream to BDNF’s neuroprotection in vivo. These findings could offer valuable insights for developing neuroprotective strategies aimed at preserving injured neurons from degeneration and promoting their regeneration.